Forsythoside B ameliorates diabetic cognitive dysfunction by inhibiting hippocampal neuroinflammation and reducing synaptic dysfunction in ovariectomized mice - Nan, Xinyu; Sun, Qi; Xu, Xiaoyu; Yang, Ying; Zhen, Yanfeng; Zhang, Yameng; Zhou, Haixia; Fang, Hui (Frontiers in Aging Neuroscience, 2022)
Background: Diabetes-associated cognitive impairment (DACI) is a common complication of diabetes, and studies have shown that DACI is more severe in postmenopausal patients with diabetes. Forsythoside B (FTS•B) can inhibit inflammation and reduce synaptic dysfunction, which can improve cognitive function. However, it has not been confirmed whether FTS•B has a reversing or retarding effect on postmenopausal diabetic encephalopathy. Methods: Seven days after bilateral ovariectomy (OVX) or sham surgery, adult female C57 mice (n = 15 per group) received intraperitoneal injection of either streptozotocin (60 mg/kg/kg/d/1) or citrate buffer for 5 consecutive days to induce diabetes mellitus (DM). Fourteen days later, ovariectomized diabetic mice were given intraperitoneal injection of FTS·B (100, 150 mg/kg/d/1) for 8 weeks (OVX+DM+L-FTS•B group and OVX+DM+H-FTS•B group). In addition, the following control groups were defined: Sham, OVX, DM, and O+D . Fasting plasma glucose was determined in each group of mice. Next, their cognitive function was tested through behavioral experiments. Hematoxylin & eosin (H&E) and Nissl staining were used to detect the morphological changes in the hippocampus. The aggregation of Aβ and the hyperaggregation of p-tau were assessed by immunohistochemistry. IL-1β, IL-6, TNF-α, brain-derived neurotrophic factor (BDNF), post-synaptic density-95 (PSD95), synaptophysin, and synapsin-1 expression in the hippocampus was detected by real-time polymerase chain reaction (RT-PCR) and western blot analysis. Results: FTS·B can decreased fasting glucose level. Behavioral results showed that cognitive decline was the most severe in ovariectomized diabetic mice and the O+D+F group revised the cognitive decline. Compared to the O+D group, more normal morphology, which has obvious nucleoli and clear nuclear membrane, was observed by H&E and Nissl staining in the O+D+F group. FTS·B alleviated DACI by reducing the aggregation of Aβ and the hyperaggregation of p-tau in the hippocampus. Moreover, the protein and mRNA expression showed that FTS·B not only inhibited inflammation by decreasing IL-1β, IL-6 and TNF-α but also modulated synaptic plasticity by increasing BDNF, PSD95, synaptophysin, and synapsin-1. Conclusions: These results suggest that FTS•B may be a novel therapeutic target for postmenopausal diabetic encephalopathy treatment.